Cause analysis of width-dependence of on-current variability in thin gate-all-around silicon nanowire MOSFET. (7th February 2022) - Liu, Zihao; Mizutani, Tomoko; Saraya, Takuya; Kobayashi, Masaharu; Hiramoto, Toshiro
Abstract: In this study, the width dependence of on-current variability in extremely narrow gate-all-around silicon nanowire MOSFET down to 2 nm width is analyzed by variability decomposition into components as well as analyzing the Pelgrom plot. It is found that the current variability rapidly increases below 4 nm mainly due to quantum-effect-induced threshold voltage variability and silicon-thickness-fluctuation-induced mobility fluctuation. The current variability becomes even worse in 2 nm, which is fundamentally caused by line width roughness.